Is the injection of DNA enough to cause bacteriophage P22-induced changes in the cellular transport process of Salmonella typhimurium? - Bandyopadhyay, P N (1979)
It was demonstrated earlier in this laboratory that phage P22 induces a transient depression in the cellular transport processes of the host Salmonella typhimurium immediately after infection and that an effective injection process is enough to cause the depression. By using defective phage particles that contain host DNA instead of phage DNA for infection, it has been demonstrated that the injection of phage-specific DNA is essential for this. The defective particles adsorbed to the host and injected their DNA, but the cellular transport processes of the host were not altered. Thus, the injection of host DNA by the phage fails to affect the transport process. Insensitivity of the phage DNA-induced depression in transport to chloramphenicol rules out the involvement of newly synthesized protein in this change and indirectly suggests the possible role of phage DNA-associated internal proteins of P22.